Metaphysical pictorial discourse in graphic design (Al-Academy, 2024)
The concept of discourse falls through the philosophy of communication and reception according to an intellectual diversity that extends from the audible to the written and the visual, and enhances the process of interaction with the reactions and reflections it achieves, and that the imaginary discourse increases the possibility of communicating messages in its various propositions and influences the perception of the recipient and stimulates the desire to deal with various topics and that this discourse may be associated with different concepts such as (metaphysics) beyond nature and reveals many cases and vague phenomena, whose topics the graphic design deals with as a philosophy A creative way to simplify those themes that are represented on the one hand by some myths and on the other hand the unlimited human imagination.